Incidence and outcomes of post-transplant lymphoproliferative disease after 5365 solid-organ transplants over a 20-year period at two UK transplant centres. - Santarsieri, Anna; Rudge, John F; Amin, Irum; Gelson, Will; Parmar, Jasvir; Pettit, Stephen; Sharkey, Lisa; Uttenthal, Benjamin J; Follows, George A (Wiley, 2022)
Post-transplant lymphoproliferative disease (PTLD) is a life-threatening complication of solid-organ transplantation (SOT). We present the incidence and outcomes of PTLD in a cohort of 5365 SOT recipients over a 20-year period at two UK transplant centres. With a median follow-up of 7.7 years, 142 of 5365 patients have developed PTLD. Cumulative incidence was 18% at five years after multivisceral transplant and 1%-3% at five years following the other SOT types. Twenty-year cumulative incidence was 2%-3% following liver and heart transplantation and 10% following kidney transplantation. Median overall survival (OS) following SOT was 16 years, which is significantly reduced compared with the age-adjusted UK population. There is relatively high early mortality following diagnosis of PTLD and only patients surviving two years regained a longer-term survival approaching the non-PTLD SOT cohort. Of 90 patients with monomorphic PTLD, diffuse large B-cell lymphoma, 66 were treated with first-line rituximab monotherapy and 24 received first-line rituximab plus chemotherapy. Up-front rituximab monotherapy does not appear to compromise OS, but the number of patients dying from non-lymphoma causes before and after treatment remains high with both treatment approaches. Multivariate analysis of all 90 monomorphic PTLD patients identified an International Prognostic Index (IPI) of 3+ as the strongest pretreatment variable associating with inferior one-year OS.
Keywords: chemotherapy; chop; ebv; epidemiology; lymphoproliferative disease; Epstein-Barr Virus Infections; Humans; Incidence; Lymphoproliferative Disorders; Organ Transplantation; Retrospective Studies; Rituximab; United Kingdom